Using evidence how research can inform public services - Nutley, Sandra ca. 20./21. Jh; Walter, Isabel 1972-; Davies, Huw T. O. 1961- (Policy Press, 2007)
This book provides a timely and novel contribution to understanding and enhancing evidence use. It builds on and complements the popular and best-selling What Works?: Evidence-based policy and practice in public services (Davies, Nutley and Smith, Policy Press, 2000), by drawing together current knowledge about how research gets used and how this can be encouraged and improved. In particular, the authors explore various multidiscipliary frameworks for understanding the research use agenda; consider how research use and the impact of research can be assessed; summarise the empirical evidence from the education, health care, social care and criminal justice fields about how research is used and how this can be improved and draw out practical issues that need to be addressed if research is to have greater impact on public services. Using evidence is important reading for university and government researchers, research funding bodies, public service managers and professionals, and students of public policy and management. It will also prove an invaluable guide for anyone involved in the implementation of evidence-based policy and practice
Title from publisher's bibliographic system (viewed on 14 Jan 2022)
Keywords: Public administration / Great Britain; Political planning / Great Britain